Design of Lampung Bay Waterfront Using Poetic Architecture Approach - Shofia Islamia Ishar; Muhammad Syahroni (Bandar Lampung University (UBL), 2014)
Lampung Bay is one of the precious natural elements in Bandar Lampung. The character, the wealth of seafood, and the beauty of the landscape are a good potency that can be synergies to the city life. Preservation and beauty of Lampung Bay may improve the environmental quality of the city so that the need to maintain its existence becomes very urgent.Unfortunately the existence of Lampung Bay has not been appreciated as a valuable natural asset. It conditions is neglected and overflowing trash. The perception that the water area as a“behind